2014
DOI: 10.1021/ie502059f
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Thermal Oil Flow Rate for Indirect Integration of Multiple Plants

Abstract: Energy integration of multiple plants may be carried out indirectly through thermal oil. Flow rate of thermal oil is related to the heat to be transferred, and it affects the capacity and power requirement of the pumps and the piping size. In this paper, a linear programming formulation is proposed to minimize the flow rate of thermal oil. The proposed formulation considers the minimum total utilities requirement for indirectly integrated multiple plants as a constraint. For the special case of two plants inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Implementation of sub-systems helped solving large-scale HLD problems, which are often computationally expensive. Bade and Bandyopadhyay [34] worked on a method to minimise the flow of a hot oil circuit between two plants. Although pumping and piping costs were not considered in the objective function, they were indirectly minimised by selecting the lowest possible hot oil flowrate.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of sub-systems helped solving large-scale HLD problems, which are often computationally expensive. Bade and Bandyopadhyay [34] worked on a method to minimise the flow of a hot oil circuit between two plants. Although pumping and piping costs were not considered in the objective function, they were indirectly minimised by selecting the lowest possible hot oil flowrate.…”
Section: State Of the Artmentioning
confidence: 99%
“…Another aspect overlooked in the literature is the type of the intermediate fluid which is used in inter-plant exchange. Methods have been specifically developed for heat sharing by steam [11], hot water [38] or hot oil [34]. Thus, the gaps in the literature are identified as:…”
Section: State Of the Artmentioning
confidence: 99%
“…Use of a fluid with a higher heat capacity will result in lower pumping costs, possibly decreased safety concerns due to spillage and simplification of control [63]. Use of heat exchange mediums other than steam, such as thermal oil to minimize the flow rate for indirect interplant integration, was investigated by Bade and Bandyopadhyay [129]. The use of heat recovery loops (HRLs) with thermal storage have been proposed for indirect heat transfer between individual plants with low pinch temperatures [130].…”
Section: Heat and Powermentioning
confidence: 99%
“…Bagajewicz and Rodera proposed an MINLP model to determine the minimum number of oil circuits in heat integration across plants. Bade and Bandyopadhyay presented an LP formulation to minimize the heat flowrate of thermal oil to transfer interplant heat at minimum total utility consumption. Based on pinch analysis, Chang et al concluded that thermal oil can transfer sensible heat and thus enhance heat recovery efficiency than steam.…”
Section: Introductionmentioning
confidence: 99%